Gastrointestinal cancer and nutrition. Issue 12 (December 1969) - Gregor, O.; Toman, R.; Prušová, F.
Abstract : The hypothesis upon which this study was based is that there is a relationship between mortality from gastrointestinal cancer and living standards. On this basis we found significant correlations between the intake of animal proteins and the mortality rates for gastric and intestinal cancer. The negative correlation coefficient (r = − 0·85) is an expression of the inverse relationship between gastric and intestinal cancer mortality rates. This inverse relationship is also expressed as the correlation between the food intake, expressed by the intake of animal protein, and the respective mortality rates. The higher the food intake, the lower the gastric cancer mortality rate but the higher the intestinal cancer mortality rate. We do not claim that this relationship discovered by correlation analysis is a causal one. On the basis of this study it cannot therefore be said that food intake has a direct effect on the development of gastrointestinal cancer. In this respect our findings can only be a signal for further studies. Secondly no time lag has been proved between food intake and the mortality rate for intestinal cancer. The findings relating to gastric cancer do not contradict the hypothesis of a time lag.